(untitled) (Ra. Revista de Arquitectura, 2020)
Humanity has succeeded to accomplish a great deal. Our evolution exhibits immense power and accomplishments. Among the wide spectrum of human achievements are symbols, paintings, language, writing, printing, Internet, architecture and design. All function as lifechanging manifestations of human intellectual achievement, amplified by multiple communication tools which have unified individuals under the tag of shared culture. The Cambridge Dictionary defines culture as “the way of life, especially the general customs and beliefs, of a particular group of people at a particular time”, but does today’s culture really reflect my deepest values and beliefs?